2006
DOI: 10.1007/s11255-006-0077-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and inflammatory status influence darbepoetin dose in pre-dialysis elderly patients

Abstract: Anaemia is a common finding in elderly patients particularly in those with chronic kidney disease. Effective correction of anaemia improves survival and quality of life. The association between anaemia and a poor nutritional status as well as the presence of inflammation has already been documented. The aim of our study was to assess the impact of the nutritional and inflammatory status on darbepoetin dose requirements of elderly patients followed in a "Chronic Kidney Disease" outpatient clinic. We included 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Several factors, such as hyperparathyroidism, aluminium intoxication, blood loss, hemoglobinopathies and hemolysis, are associated with ESA resistance [11]. Moreover, inflammation and malnutrition have been also described as factors that can be associated with anemia and can influence the ESA dose in patients with CKD [12][13][14][15][16]. On the other hand, recent studies indicated that the resistance to ESA [17,18], evaluated by the ESA resistance index [19] is associated with a higher risk of death in renal patients [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors, such as hyperparathyroidism, aluminium intoxication, blood loss, hemoglobinopathies and hemolysis, are associated with ESA resistance [11]. Moreover, inflammation and malnutrition have been also described as factors that can be associated with anemia and can influence the ESA dose in patients with CKD [12][13][14][15][16]. On the other hand, recent studies indicated that the resistance to ESA [17,18], evaluated by the ESA resistance index [19] is associated with a higher risk of death in renal patients [20].…”
Section: Introductionmentioning
confidence: 99%
“…Neves et al [40] investigated the impact of nutritional and inflammatory status on darbepoeitin dose requirements of 71 patients aged C65 years followed for 12 months in a pre-dialysis CKD clinic. Patient age ranged from 65 to 96 years (mean 76.2 ± 6.6 years).…”
Section: Management Of Anemia and Other Ckd Comorbiditiesmentioning
confidence: 99%
“…Using tissue reconstitution experiments with single hematopoietic stem cells (HSC), Ogawa et al [16] showed that HSC significantly contribute to myofibroblast population in tissues. Erythropoietin (EPO), parathyroid hormone (PTH), iron overload state, and an oxidative stress-induced ''stimulated hematopoietic environment'' [17][18][19][20][21][22] may thus contribute to fibrosis through increased production of tissue myofibroblasts. It is likely that both resident fibroblasts and diverse types of bone-marrow-derived cells that are released in response to injury and cytokines such as EPO, including HSC, endothelial progenitor cells, mesenchymal precursors, and monocyte-derived cell fibrocytes contribute to fibrogenesis in NSF (see Fig.…”
Section: Pathophysiologymentioning
confidence: 99%
“…It is a potent cytokine with stimulatory effects on vascular endothelium, smooth muscle cells, and platelets [41][42][43][44]. EPO is also a potent stimulant of endothelial and progenitor cell proliferation as well as wound healing responses that are reminiscent of histological changes seen in NSF [18,45,46], EPO [18,45,47], and PTH [19] are also strong stimuli for a systemic release of CD34 + progenitor cells, which are known to participate in wound healing [16, 19,48]. Chronic inflammation [49] associated with an EPO resistant and high-dosage EPO [43,50] might also contribute to the fibrogenesis seen in NSF.…”
Section: Host-related Factorsmentioning
confidence: 99%